The minimum number of members required to form a cooperative in Argentina: Theoretical and practical foundations for a current debate - Sosa, Gustavo Alberto; Fernández Miranda, Rodrigo (Cooperativismo & Desarrollo, 2025)
This article critically analyzes recent changes in the minimum membership requirement for establishing worker cooperatives in Argentina. The article explores the different ways these changes impact the creation, operation, and sustainability of cooperative entities. The article discusses the Cooperative Law, the evolution of the implementing authority’s resolutions regarding minimum membership requirements for these organizations in recent years, and specialized literature.
Keywords: Worker cooperatives; Minimum membership requirement; Self-management; Argentine legal framework